The family doctor in the jurisprudence of medical disciplinary boards. Analysis of select cases - Wrześniewska-Wal, Iwona (Family Medicine & Primary Care Review, 2018)
The increase in the number of malpractice actions for damages before civil courts is linked not only to patients’ increasing awareness of their rights, but also to the rapid development of medical science and new technologies, as well as the associated risk. At present, besides expert medical knowledge, a medical practitioner must have basic knowledge of the law. This article outlines, on the basis of the jurisprudence of medical disciplinary boards, the rules for medical practice that are grounded not only in the provisions of the law, but also in professional deontology. The essential rule that a practitioner may never forget at any stage of professional activity is the principle of due diligence. Examples from medical disciplinary boards cited below show that, in practice, this principle, being so fundamental to the medical profession, is violated in more than 60% of the cases at hand. These include cases involving family doctors and those practising in primary care. Medical disciplinary proceedings are brought by the disciplinary prosecutor (Rzecznik Odpowiedzialności Zawodowej), who, if convinced that professional misconduct has occurred, requests the medical disciplinary board for punishment. In regulating the disciplinary proceedings, the lawmaker provided for two instances: regional medical disciplinary board (Okręgowy Sąd Lekarski) rules in the first instance, and the Chief Medical Disciplinary Board (Naczelny Sąd Lekarski) hears the appeals. At present, one can also challenge the latter’s rulings with an appeal-in-cassation to the Supreme Court, where professional judges decide upon the case.